Znacilnosti posameznih aktivnih faz v odvisnosti od kakovostne ravni v padel igri - Ramon-Llin, J.; Guzman, J. F.; Llana, S.; James, N.; Vuckovic, G. (Kinesiologia Slovenica, 2017)
The analysis of match performance, movement and shots, can identify the variables that distinguish performance levels in sport and are of particular importance in planning training schedules. National (n=20), Regional (n=20) and Recreational (n=20) padel players were compared in competition matches (n=15) filmed by two video cameras and analysed using the SAGIT tracking system. National players have significantly higher (p <.05) speed of movement and rate of play (shots per second) compared to Regional players. Recreational players significantly (p <.001) differed from the other two levels on rally time (s), number of shots per point, distance covered, rate of play, speed during active play and the proportion of time spent at different movement intensities. The highest-level players tended to play more at the net (volley, tray and smash) and returned more using wall shots (back, side and doubles). These finding provide a guide for players aspiring to improve their performance by focussing on the characteristics that determine successful performance. Future studies need to consider how tactics impact on performance, in particular the variation in match characteristics depending on rally duration.